Front Office Communication Management in Handling Guest Complaints at Three-Star Hotels in Bogor - Sulastri, Sulastri; Hengky, SH (Finance : International Journal of Management Finance, 2025)
The hospitality enterprise is fantastically depending on effective verbal exchange between team of workers and guests, specifically within the coping with of court cases that immediately have an effect on consumer pride and loyalty. In three-big name hotels, in which provider requirements are moderate however opposition is severe, the front office performs a vital role because the primary factor of touch for guests. This study aims to research the effectiveness of the front workplace verbal exchange control—especially readability, empathy, and responsiveness—in coping with visitor complaints at 3-celebrity hotels in Bogor. A quantitative, explanatory studies design was employed, related to one hundred twenty respondents (eighty guests and forty front office group of workers) from 5 lodges. statistics have been amassed thru a established questionnaire and analyzed the use of SPSS 26.zero, with descriptive facts, one-manner ANOVA, and put up-hoc Tukey tests. The consequences imply that empathy and clarity are the most powerful predictors of guest pleasure, at the same time as responsiveness, although superb, showed relatively decrease performance. The ANOVA consequences in addition discovered huge differences in delight across distinct stages of communication effectiveness, with the biggest gap among low and excessive stages. those findings verify that powerful conversation control is a essential determinant of carrier recovery success. The study contributes theoretically by way of reinforcing verbal exchange’s function as a critical detail of provider nice and criticism dealing with, and almost by means of imparting inn managers with actionable pointers for training, popular procedures, and remarks structures. improving conversation control within the front office is therefore no longer most effective a means of resolving court cases however additionally a strategic technique to enhancing visitor pleasure, building loyalty, and ensuring competitiveness inside the hospitality sector